2018
DOI: 10.1007/s12015-018-9851-8
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Isogenic Controls for In Vitro Disease Modelling of X-Chromosomal Disorders

Abstract: Generation of proper controls is crucial in induced pluripotent stem cell (iPSC) studies. X-chromosomal disorders offer the potential to develop isogenic controls due to random X-chromosomal inactivation (XCI). However, the generation of such lines is currently hampered by skewed X-inactivation in fibroblast lines and X-chromosomal reactivation (XCR) after reprogramming. Here we describe a method to generate a pure iPSC population with respect to the specific inactivated X-chromosome (Xi). We used fibroblasts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 34 publications
(19 reference statements)
0
22
0
Order By: Relevance
“…RTT patient and iCTR fibroblasts were reprogrammed into iPSCs via electroporation of reprogramming plasmids as published before [24]. Pluripotency was confirmed using the PluriTest analysis ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…RTT patient and iCTR fibroblasts were reprogrammed into iPSCs via electroporation of reprogramming plasmids as published before [24]. Pluripotency was confirmed using the PluriTest analysis ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…So far, only a few proteomic studies have been performed on RTT human derived tissue [19, 30, 31]. The current study provides mass spectrometry-based quantitative proteomic data, depth of about 7000 proteins, using an earlier developed iPSC-based models involving RTT patient cells and isogenic controls [24]. We showed that changes in dendrite morphology or synaptic defects, previously associated with RTT [22, 32], already become apparent at early developmental stages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…cells expressing the healthy X-chromosome, fibroblasts were detached from cell culture plate and single fibroblasts were seeded in a 96-well plate. Cells were further expanded and characterized for their MeCP2 state by immunocytochemistry and PCR [24]. All of our experiments were exempt from the approval of the institutional review board.…”
Section: Cell Culture and Isogenic Controlsmentioning
confidence: 99%
“…RTT patient and iCTR fibroblasts were reprogrammed into iPSCs via electroporation of reprogramming plasmids [24]. Pluripotency was confirmed using classic assays, including immunocytochemistry (Additional file 1: Figure S1a) and RNA expression (Additional file 1: Figure S1b).…”
Section: Generation Of Ipsc-derived Neuronal Progenitors From Rtt Andmentioning
confidence: 99%